Perkembangan Literasi Digital dalam Pendidikan: Sebuah Tinjauan Bibliometrik - Sri Astuti Iriyani; Daindo Milla; Yulius Keremeta Lede; Kholidi (Indo-MathEdu Intellectuals Journal, 2023)
The development of digital literacy in education in Indonesia is an integral part of efforts to prepare the younger generation to face the growing digital era. This study aims to provide a comprehensive bibliometric analysis of literature related to the development of digital literacy in education in Indonesia. This bibliometric analysis uses the Vosviewer tool. From the Google Scholar database, we identified 995 literature sources published between 2012 and 2023.The results show that the number of publications has increased every year in the 2012-2023 time frame. Network visualization shows that research trends related to the development of digital literacy in education in Indonesia during the period include keywords such as Literacy, Technology, Literacy Ability, Data, and Teachers.  The analysis results also resulted in 16 clusters, Cluster 1 (17 items), Cluster 2 (12 items), Cluster 3 (11 items), Cluster 4 (9 items), Cluster 5 (8 items), Cluster 6 (8 items), Cluster 7 (8 items), Cluster 8 (6 items), Cluster 9 (6 items), Cluster 10 (6 items), Cluster 11 (5 items), Cluster 12 (5 items), Cluster 13 (5 items),  Cluster 14 (4 items), Cluster 15 (4 items), Cluster 16 (3 items). This study provides information to education researchers related to digital literacy in education which is expected to strengthen further research topics